Preparation of cobalt-containing spinel oxides as novel adsorbents for efficient phosphate removal. Issue 10 (10th September 2018) - Li, Ting; Liao, Taiwan; Su, Xiangde; Yu, Xiang; Han, Boping; Zhu, Yi; Zhang, Yuanming
Abstract : We prepared a series of novel and efficient phosphate removal adsorbents, figured out the adsorption mechanism in depth and revealed the relationship between the properties of adsorbents and their adsorption capacity. Abstract : In this paper, a series of cobalt-containing spinel oxides MCo2 O4 (M = Mg, Mn, Cu) were prepared by a solution combustion method and used as novel adsorbents for phosphate for the first time. MgCo2 O4 exhibited the highest adsorption capacity of up to 90.02 mg g −1, which was much greater than that of MnCo2 O4, CuCo2 O4 and most phosphate adsorbents. The adsorption isotherm and kinetics of MgCo2 O4 followed the Langmuir monolayer model and the pseudo-second-order model, respectively. The phosphate adsorption of MgCo2 O4 was found to be endothermic and nonspontaneous. Coexisting ions Cl −, NO3 −, SO3 2−, and HCO3 − did not affect the adsorption of phosphate on MgCo2 O4, but the presence of CO3 2− would significantly interfere with the adsorption. Little decrease in removal efficiency after three adsorption–desorption cycles suggested its excellent stability and recyclability. Leakages of Co 3+ and Mg 2+ from MgCo2 O4 were negligible when pH was higher than 3.0 during the adsorption process. The mechanism study revealed that the adsorption mechanism involved precipitation, electrostatic interaction and ligand exchange. The large surface area, high surface hydroxyl group content and more positive zeta potential resulted in high adsorption capacity. This work provided an excellent reference to constructing novel phosphate adsorbents and a deep insight into the study of the phosphate adsorption mechanism.